PARADIGMA PENGGUNAAN MEDIA SOSIAL DALAM PERSPEKTIF MAHASISWA PROGRAM STUDI PENDIDIKAN AGAMA ISLAM UNIVERSITAS SINGAPERBANGSA KARAWANG - Zaenul Fikri Laksana, Mohammad; Achmad Junaedi Sitika; Agus Susilo Saefullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study describes the paradigm of social media use from the perspective of students of the Islamic Religious Education Study Program at Universitas Singaperbangsa Karawang. This research uses a descriptive qualitative approach. Data were collected through observation, semi-structured interviews, documentation, and supporting questionnaires, then analyzed through data reduction, data display, and conclusion drawing. The findings show that students generally view social media as a communication tool, information source, learning medium, discussion space, and means of digital da’wah. The most frequently used platforms are WhatsApp, Instagram, TikTok, YouTube, and Facebook. Students also recognize negative impacts, including hoaxes, learning distraction, decreased productivity, excessive entertainment consumption, and reduced worship focus. From the perspective of Islamic education, students emphasize honesty, responsibility, politeness, self-control, and tabayyun as ethical principles. Social media can support Islamic education when it is used critically, proportionally, and in accordance with Islamic values.